1983
DOI: 10.1620/tjem.140.407
|View full text |Cite
|
Sign up to set email alerts
|

Difference in mode of action of cimetidine ane gefarnate on endogenous prostacyclin, prostaglandin E2 and thromboxane in rat gastric mucosa.

Abstract: The effects of cimetidine and gefarnate on endogenous prostacyclin, prostaglandin E2 and thromboxane were studied in vivo in rat gastric mucosa. The animals received cimetidine (20 mg/kg, i.p.) and/or gefarnate (100 mg/kg, s.c.) twice a day for 7 days. Gastric mucosal 6-keto-prostaglandin F1 (as prostacyclin), prostaglandin E2 and thromboxane B2 (as thromboxane A2) were determined by radioimmunoassay. Cimetidine reduced prostacyclin, prostaglandin E2, but not thromboxane A2. Gefarnate inhibited the cimetidine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Prostaglandins that show "cytoprotective" effects against gastric damage induced by nox ious agents (2) have been recognized as im portant defensive factors. It has been sug gested that CIM decreases PG production in the rat (8). On the other hand, Branski et al demonstrated that PG in the gastric mucosa of patients, suffering from duodenal ulcers, was significantly increased after CIM treatment (5).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins that show "cytoprotective" effects against gastric damage induced by nox ious agents (2) have been recognized as im portant defensive factors. It has been sug gested that CIM decreases PG production in the rat (8). On the other hand, Branski et al demonstrated that PG in the gastric mucosa of patients, suffering from duodenal ulcers, was significantly increased after CIM treatment (5).…”
Section: Discussionmentioning
confidence: 99%
“…According to Arakawa et al (6), cimetidine administered to rats twice a day for 7 days at a daily dose of 40 mg/kg decreased PGE2 and PGF1a in the gastric mucosal tissue. By con trast, Branski et al (5) reported that the ac cumulation of PGE2 and PGF1a in the biopsy specimens from the stomach of ulcer patients was significantly increased after 4 weeks of cimetidine treatment at a daily dose of 1 g. Okada et al (10) also showed that the PGE2 level in the gastric mucosa of rats exposed to restraint and water-immersion stress was elevated by 25 mg/kg of oral cimetidine.…”
mentioning
confidence: 99%